Updated Role of Neuropeptide Y in Nicotine-Induced Endothelial Dysfunction and Atherosclerosis - Zheng, Yan-li; Wang, Wan-da; Li, Mei-mei; Lin, Shu; Lin, Hui-li (Frontiers in Cardiovascular Medicine, 2021)
Cardiovascular disease is the leading cause of death worldwide. Endothelial dysfunction of the arterial vasculature plays a pivotal role in cardiovascular pathogenesis. Nicotine-induced endothelial dysfunction substantially contributes to the development of arteriosclerotic cardiovascular disease. Nicotine promotes oxidative inflammation, thrombosis, pathological angiogenesis, and vasoconstriction, and induces insulin resistance. However, the exact mechanism through which nicotine induces endothelial dysfunction remains unclear. Neuropeptide Y (NPY) is widely distributed in the central nervous system and peripheral tissues, and it participates in the pathogenesis of atherosclerosis by regulating vasoconstriction, energy metabolism, local plaque inflammatory response, activation and aggregation of platelets, and stress and anxiety-related emotion. Nicotine can increase the expression of NPY, suggesting that NPY is involved in nicotine-induced endothelial dysfunction. Herein, we present an updated review of the possible mechanisms of nicotine-induced atherosclerosis, with a focus on endothelial cell dysfunction associated with nicotine and NPY.